Anaerobic treatment of propylene glycol-contaminated domestic wastewater and microbial community profile at threshold ratio. Issue 2 (February 2021) - Yangin-Gomec, Cigdem; Engiz, Gizem
Abstract: An up-flow anaerobic sludge bed (UASB) reactor was operated for five months to treat domestic wastewater contaminated by propylene glycol -main component of Type 2 aircraft deicing fluid (ADF)- at threshold ratio based on optimization study with batch reactors [i.e., operated at externally included ADF = 0.83–4.20%]. Biogas yields up to 0.4 m 3 /kg CODinfluent was achieved, however drastically reduced along with total chemical oxygen demand (tCOD) removal at ADF>1.20% and indicated strong inhibition. Hence, the UASB reactor was fed at ADF = 1.05% [tCODinfluent = 8930 ± 2100 mg/L] and yielded >80% tCOD removal on average. Next generation sequencing (NGS) findings also revealed that Firmicutes and Bacteroidetes had the highest ratios of relative abundances in biomass sample taken at the last operating day; hence co-existence of these phyla played significant role in glycol removal with Synergistetes and Thermotogae bacteria whereas Methanobacterium and Methanoculleus archaea increased remarkably. Abstract : Aircraft deicing fluid; Biogas; Glycol; Predominant species; Toxicity; UASB reactor.